Pengaruh Komunikasi Visual X-Banner Berbusana Muslimah terhadap Praktik Hijab Menutup Dada - Septa Adistya Kusnandar Syahputri; Parihat Kamil; Hendi Suhendi (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. Visual communication serves as an important medium for conveying institutional policies in academic environments. At Universitas Islam Bandung (UNISBA), X-Banners are used to communicate guidelines on Muslim women’s dress, particularly the requirement to wear a hijab that covers the chest. However, differences between the intended message and its implementation among female students are still observed. This study aims to identify the form of visual communication used in the X-Banner and examine its influence on the practice of wearing a chest-covering hijab among Psychology students of the 2022 cohort. Using a quantitative approach with an explanatory survey method, data were collected from 70 respondents selected through the Slovin formula. Data collection employed Likert-scale questionnaires, supported by documentation and literature review. Analysis included validity and reliability tests, classical assumption tests, and simple linear regression. The results show that the X-Banner’s visual communication is perceived as clear, relevant, and easy to understand. Furthermore, visual communication has a positive and significant effect on the practice of wearing a chest-covering hijab, with a coefficient of determination of 40.5%. These findings indicate that visual communication contributes to shaping students’ dress practices, although other factors also influence behavior. Abstrak. Komunikasi visual merupakan sarana penting dalam penyampaian kebijakan institusi di lingkungan akademik. Universitas Islam Bandung (UNISBA) memanfaatkan media X-Banner untuk mensosialisasikan aturan berbusana Muslimah, khususnya penggunaan hijab yang menutup dada. Namun, masih ditemukan perbedaan antara pesan yang disampaikan dan penerapannya di kalangan mahasiswi. Artikel ini bertujuan mengidentifikasi bentuk komunikasi visual pada X-Banner serta menguji pengaruhnya terhadap praktik hijab menutup dada pada mahasiswi Fakultas Psikologi Angkatan 2022. Artikel menggunakan pendekatan kuantitatif dengan metode explanatory survey terhadap 70 responden yang ditentukan melalui rumus Slovin. Data dikumpulkan menggunakan kuesioner skala Likert, dokumentasi, dan studi pustaka. Analisis data meliputi uji validitas, reliabilitas, asumsi klasik, dan regresi linear sederhana. Hasil artikel menunjukkan bahwa komunikasi visual X-Banner dinilai jelas, relevan, dan mudah dipahami. Selain itu, komunikasi visual tersebut berpengaruh positif dan signifikan terhadap praktik hijab menutup dada dengan koefisien determinasi sebesar 40,5%. Temuan ini menunjukkan bahwa komunikasi visual berkontribusi dalam membentuk praktik berbusana mahasiswi, meskipun terdapat faktor lain yang turut memengaruhinya.